Household Registration System Reform and Firm Innovation: Evidence from China's Scaled Industrial Firms - Zhang, Fuxing; Yuan, Yan; Rong, Wanting (Emerging markets finance & trade, 2023)
China has relaxed its household registration system (HRS), making it easier for rural-to-urban migrants to settle in cities. By improving the stability of high-educated workers in firms, the HRS reform should enhance these firms' innovation. We investigate how the HRS reform influenced scaled industrial enterprises' innovation by exploiting the staggered HRS reform in different cities from 1998 to 2007. We find that the HRS reform significantly increased these firms' innovation output, measured by patent counts. We further find that this positive effect mainly existed among knowledge-intensive firms.